2009
DOI: 10.1080/02701367.2009.10599556
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Motor Skill Competence and Physical Fitness in Young Adults

Abstract: We examined the relationship between competence in three fundamental motor skills (throwing kicking, and jumping) and six measures of health-related physical fitness in young adults (ages 18-25). We assessed motor skill competence using product scores of maximum kicking and throwing speed and maximum jumping distance. A factor analysis indicated the 12-min run/walk, percent body fat, curl-ups, grip strength, and maximum leg press strength all loaded on one factor defining the construct of "overall fitness. "Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
161
4
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 16 publications
10
161
4
19
Order By: Relevance
“…During these years children learn the basic types of motor skills like running and hopping which promotes the process of development of their basic motor abilities, such as speed, strength, coordination and balance (Sentderdi, 2008). These skills and abilities are the foundations of a variety of physical activities (Gallahue, 2006) and may influence later physical activity levels in adolescence and adulthood (L. M. Barnett, van Beurden, Morgan, Brooks, & Beard, 2009;Stodden, Langendorfer, & Roberton, 2009). Children with higher levels of motor skill performance are more physically active than those with less well developed skills (Fisher et al, 2005;Laukkanen, Pesola, Havu, Saakslahti, & Finni, 2014;Williams et al, 2008;Wrotniak, Epstein, Dorn, Jones, & Kondilis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…During these years children learn the basic types of motor skills like running and hopping which promotes the process of development of their basic motor abilities, such as speed, strength, coordination and balance (Sentderdi, 2008). These skills and abilities are the foundations of a variety of physical activities (Gallahue, 2006) and may influence later physical activity levels in adolescence and adulthood (L. M. Barnett, van Beurden, Morgan, Brooks, & Beard, 2009;Stodden, Langendorfer, & Roberton, 2009). Children with higher levels of motor skill performance are more physically active than those with less well developed skills (Fisher et al, 2005;Laukkanen, Pesola, Havu, Saakslahti, & Finni, 2014;Williams et al, 2008;Wrotniak, Epstein, Dorn, Jones, & Kondilis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The suggested four factors could be viewed as broader aspects of movement skills in the growth and refinement phase (Gabbard, 2004) and specialized movement phase (Gallahue & Ozmun, 1998) in relation to the already established basic movement categories of locomotor, object control, and stability skills in the fundamental movement skills (FMS) phase. The component of strength in Factor 1, here labeled strength and coordination skills , have in previous research shown to be related to good results in movement skill testing (e.g., Haga, 2008;Hands et al, 2009;Stodden et al, 2009;Thomas & French, 1985). A component of strength can be understood as an important part in movement skill development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a number of studies conducted on adolescents and young adults, researchers have measured a limited number of movement skills (Stodden, et al 2009;Jaakkola, Kalaja, Liukkonen, Jutila, & Virtanen, 2009).These assessments have all been product-oriented. A number of shortcomings with product-oriented assessment have been addressed in the literature, including the problems of measuring quantitative aspects such as speed, height, length, or number of failed attempts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Střední až vysoká úroveň ovladatelnosti hrubých pohybových dovedností potřebná pro úspěšnou účast v mnohých sportech a druzích PA může být vztažena k vyšší úrovni výkonnosti a zdravotně orientované zdatnosti (ZOZ). Na provádění hrubých pohybových dovedností se podílí dostatečně vysoká úroveň kardiorespirační a svalové vytrvalosti, které spolu s optimální úrovni BMI tvoří základní komponenty ZOZ (Stodden, Langendorfer, & Roberton, 2009). Rozvoj hrubých pohybových dovedností během dětství pomocí nejpestřejších forem PA může představovat základ pozitivního trendu rozvoje TZ a pohybových návyků během dětství, dospívání a dospělosti (Stodden et al, 2008).…”
unclassified